Exploring the half-metallic ferromagnetism, dynamical and mechanical stability, optoelectronic and thermoelectric properties of K2NaMI6 (M = Mn, Co, Ni) for spintronic applications - Danish Abdullah; Dinesh C. Gupta (Scientific Reports, 2023)
Abstract The structural stability, optoelectronic and magnetic characteristics of K2NaMI6 (M = Mn, Co, and Ni) halide double perovskites have been demonstrated to be explained using density functional theory computations. The prominent generalized gradient approximation and integration of the mBJ potential are implemented to estimate the exchange–correlation potential, which is the only unidentified parameter in the state-of-the-art formulism. The structural optimization, mechanical stability criteria, and tolerance factor demonstrate the reliability of the double perovskites in a cubic structure with Fm3m symmetry. The elastic constants facilitated mechanical stability and revealed the brittle nature of these double perovskites. The spin-polarized electronic band profile and the behaviour of the dielectric constant and absorption coefficient in the spin-up and down channels show the presence of half-metallic nature in these materials. Additionally, we examined magnetism and the genesis of the half-metallic gap in this article. The half-metallic and magnetic properties are attributed to the unpaired electrons in the split d-orbitals of the M-sited elements in the crystal field. The Mn-, Co-, and Ni-based double perovskites were found to possess total magnetic moments of 4 μB, 4 μB, and 1 μB, respectively, with the transition metal atoms comprising up the majority of this magnetic moment. The Fermi level’s perfect spin polarisation promotes the potential application of double perovskites in spintronic technology.